The relationship between sport management and the field of disability: A bibliometric analysis - González-García, Rómulo Jacobo; Martínez-Rico, Gabriel; Martínez-Basomba, Jorge; Pérez-Campos, Carlos (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The relationship between sport management and the disability field has been gaining interest in recent years. The number of people with disabilities playing sport has increased significantly, and the objectives of sport management have focused on promoting participation and improving the health and well-being of people with disabilities. This paper analyses the articles published in the Web of Science on the practice of sport for people with disabilities and the field of sport management. Bibliometric analysis allows us to discover the current state of a research field, identify the main authors, articles and topics, and propose future lines of research to develop it further. Articles published between 1999 and 2022 were analysed quantitatively and by co-occurrence of words and authors. Subsequently, through bibliographic linking, the articles were grouped into different clusters. Four central themes were found, with the areas of marketing and sport events being the most developed. This study provides a basis for future research on sport for people with disabilities in the field of sport management. The results of this study can help to improve the participation of people with disabilities in sport, and improve their health and well-being.